Diseño de un sistema para tratamiento de aguas residuales industriales, para el proceso de elaboración de adhesivo de almidón (goma) en la industria "Cartones Nacionales Cartopel S.A.I." - Vera Galarza, Kasandra Adriana (2018)
The purpose of this research work is to collaborate with the Enterprise Cartopel S.A.I, with the proposal to design a system for industrial wastewater treatment and reuse them in the subprocess of the manufacture of starch (rubber) adhesive. The treatment basically consists of a physical-chemical treatment. To determine the dose of efficient coagulants and flocculants, jar test tests were carried out at the laboratory level, consecutively the unit operations that intervene in the system were analyzed. Finally, a benefit / cost analysis was carried out in order to demonstrate the feasibility and profitability of the implementation. The environmental and economic benefits of this project are based on the minimization of operating costs, better management of water resources, and reduction of environmental impact.